2008
DOI: 10.1021/jo702551t
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki−Miyaura Approach to JNJ-26076713, an Orally Active Tetrahydroquinoline-Containing αVβ3Vβ5 Integrin Antagonist. Enantioselective Synthesis and Stereochemical Studies

Abstract: An improved scale-up synthesis was required for the alpha(V)beta(3)/alpha(V)beta(5) integrin antagonist 1, which had demonstrated oral efficacy in eye disease models of angiogenesis and vascular permeability. A stereodefined, quinoline-substituted, unsaturated ester was conveniently prepared by a Suzuki-Miyaura coupling to facilitate exploration of multiple methods of asymmetric reduction. The catalytic chiral hydrogenation of the corresponding unsaturated acid (Z-5b) with a ruthenium-based metal precursor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Acting as chemotherapeutic targets . Tetrahydroquinoline analogous have been cited as anti‐HIV compound 12 [147–153], antibacterial compounds 13–15 , [154–156], antifungal compound 16 [157–160], antimalarial compounds 17 – 19 [161–168], and antitumor compounds 20–24 [169–179] (Figures 3 and 4).…”
Section: The Strategies For Hydrogenationmentioning
confidence: 99%
“…Acting as chemotherapeutic targets . Tetrahydroquinoline analogous have been cited as anti‐HIV compound 12 [147–153], antibacterial compounds 13–15 , [154–156], antifungal compound 16 [157–160], antimalarial compounds 17 – 19 [161–168], and antitumor compounds 20–24 [169–179] (Figures 3 and 4).…”
Section: The Strategies For Hydrogenationmentioning
confidence: 99%
“…40 The tetrahydroquinoline intermediate to an integrin antagonist could be obtained as a mixture of diastereoisomers via achiral reduction of the heterocyclic ring of the corresponding chiral quinolone (eq 16). 41 Asymmetric reductions of heteroaromatics have been well documented, 42 with examples including preparation a range of tetrahydroquinoline species in high ee (eq 17). 43 Furthermore, phosphine-free asymmetric hydrogenations of quinolines have also been reported.…”
Section: Carbon-carbon Bond Reductionsmentioning
confidence: 99%
“…There were cost savings for the lower catalyst usage with a cheaper metal that outweighed the need to perform two extra steps. 169,170 Further studies of the reaction parameters showed that when {Ru[(R)-XylPhanePhos]Cl 2 (DMF) n } was used as the catalyst precursor, then triethylamine had to be added to obtain good substrate : catalyst ratios. The maximum was observed around 0.5 equivalents of the base and this was explained by activation of the catalyst; the quinoline moiety within the substrate being basic enough to deprotonate the carboxylic acid.…”
Section: Substrate Screeningmentioning
confidence: 99%